News Media Power and Public Policy: The Mediatized Construction of Women Trafficking for Sexual Exploitation - Simões, Rita Basílio de (2018)
Like other areas of violence against women, sex trafficking has become in the last decade increasingly politicized in Portuguese society, with the news media attaching important visibility to it, both for public awareness purposes and government reaction. This happened after the dismantling of a chain of striptease clubs, suspected of hosting trafficking activities. Known as the “Passerelle case”, this event attracted great media attention and brought to the public sphere the problem of trafficking in women for sexual purposes. This article looks at the Portuguese press to understand in what ways the news coverage of the case paved the way for the social and political acknowledgment of this issue, and to what extent it favored an understanding capable of making a real difference in the lives of women. It argues that, despite the news media’s undeniable involvement in sociopolitical changes claimed by feminism, its emancipatory potential remained unexplored.